Using Building Information Modeling to Enhance Supply Chain Resilience in Prefabricated Buildings: A Conceptual Framework - Yuanyuan Hua; Ying Zhang; Sujuan Zhang; Fengmin Hou; Manlin Kang (Applied Sciences, 2023)
Prefabricated buildings usually involve various project participants and complicated processes of design, manufacturing, transport, assembly, and construction, which means they constantly face supply chain disruptions. As a tool to realize information integration and facilitate communication among project participants in the supply chain, building information modeling (BIM) is widely recognized as an important technology to foster supply chain resilience. However, it is unclear how BIM can facilitate supply chain resilience in prefabricated buildings. This study aims to construct a conceptual framework to better understand the influencing paths of BIM on supply chain resilience in the context of prefabricated buildings. It employs an integrative review method to identify key factors influencing the resilience of the prefabricated building supply chain and explore the effects of BIM on these factors. The role of BIM in linking these factors was verified through an empirical case. The results show that BIM resources and capabilities can enhance supply chain resilience by influencing participant factors (assembly construction capability, design capability) and partnership factors (information sharing, cooperation, coordination, and trust). This study incorporates supply chain resilience and BIM technology into a conceptual framework in the context of prefabricated buildings, providing new theoretical insights for future supply chain management.